Design of planar slider-rocker mechanisms for imposed limit positions, with transmission angle and uniform motion controls. (March 2016) - Simionescu, P.A.
Abstract: One possible way of converting the displacement of a linear motor into oscillatory motion of an output member is through the use of the planar slider-rocker mechanisms or PRRR in short. In this paper, the optimum synthesis of the PRRR mechanism for prescribed limit positions and best transmission angle characteristics (with and without ensuring uniform input–output motion) is considered. Systematic investigations of the design space in the respective optimization problems reveal some remarkable properties of this mechanism with potential new applications. To assist practicing engineers with selecting the link lengths of a PRRR mechanism, performance charts and parametric design charts are also provided. Highlights: The RPRR mechanism is optimized for given limit positions and motion efficiency, with or without linear IO correlation. The design space of the optimization problem is investigated using partial-global minima plots. Parametric design charts and performance charts are provided to assist the practicing engineer. Several possible applications are suggested throughout the paper and in an appendix.